Face shape recognition for hairstyle recommendation using MATLAB / Muhammad Azizi Nordin - Nordin, Muhammad Azizi (2015)
Nowadays, hairstyle is one of the fashions that can bring the image of the face and whole attire. One of way to choose a suitable hairstyle is by considering the shape of the face. If the hairstyle been form perfectly but does not suitable with the face shape still could make a terrible image. Based on observation, 61 percent of people did not know their own face shape. This project is built to help the user to find the face shape by applying modern technology which is image processing. This project also provides suggestion of suitable hairstyle base on the face shape. The technique will be used is Canny edge detection and the platform will be MATLAB. The technique is chosen because of its accuracy in detecting the edge of image than using other techniques which are Sobel, Prewitt and Robert. Development method that suitable for this research project which has six phases is agile method because of its flexibility in developing a project. The focus in this technique is the Edge detection which needed to find the image information to determine the shape of the face. As a conclusion, this research would give some benefits in image processing area. Other researchers can make some enhancement in the future in order to improve this research. The system can be improved by better input and output of the project and also develop for mobile application for the future work.